(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article discusses the negative impact of energy drinks on developing teeth. The acidic environment and high sugar content in energy drinks can lead to enamel erosion and disruption of the mineralization process. Special attention is given to preventive measures to minimize dental damage.